PENGARUH HUTANG DAN MODAL TERHADAP PROFITABILITAS (RISET PADA PT LIPPO KARAWACI TBK) - Ma'wa, Nurul Jannatul; Alwi , Alwi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
Abstract The purpose of this research is analyze the influence of debt and capital on the probability of PT Lippo Karwaci,tbk. The indicator to measure profitability using Return to Asset (ROA). Whereas, the debt using the TTD Ratio and capital ratio using debt to equity ratio (DER). The type of this research is associative. The sample of this research ten years long started from 2009-2018. The data used in this study is to use the company’s financial statement data published on the Bursa Efek Indonesia’s (BEI) website. The data used are secondary, and the method used is regression analysis that is time-series data with the help of SPSS version 20.0 to get a description of the relationship between variables.